The Relationship of Working Period and Awards with The Caring Behavior of Nurses - Yunita, Siti Dwi; Aprina, Aprina; Sunarsih, Sunarsih (Jurnal Kesehatan, 2025)
Caring behavior involves actions rooted in concern, compassion, skill, empathy, responsibility, sensitivity, and support. Previous studies have indicated that many nurses do not exhibit caring behavior, which is influenced by various factors. Research at RSUD Abdul Moeloek revealed that care was primarily focused on physical ailments, with limited nurse presence and inadequate psychological support for patients. Among the 10 respondents, 75% noted that nurses did not display caring behaviors, such as presence, touch, listening, and understanding, while 25% did. This study aims to examine the relationship between work experience and awards with the caring behavior of nurses in the Internal Medicine ward at RSUD Dr. H. Abdul Moeloek, Lampung. Conducted from March to April 2024, this quantitative research used a descriptive-analytic design with a cross-sectional approach. A total of 33 respondents were selected through total sampling. Data were collected using questionnaires completed by respondents and researchers. The relationship between independent and dependent variables was tested using the Chi-square test, with univariate and bivariate analysis. Results showed a significant relationship between work experience (p-value=0.007, OR=19.429) and awards (p-value=0.003, OR=13.750) and nurses' caring behavior. It is recommended that the hospital enhance service quality, especially through training, to improve nurses' caring and friendliness towards patients.